Gone - Hayder, Mo (Atlantic Monthly Press, 2010)
Investigating a serial carjacker whose actual targets are young children in back seats, Jack Caffery teams up once again with police diver Sergeant Flea Marley, whose life is endangered by a discovery in an abandoned, half-submerged tunnel.